Changes in Antithrombotic Therapy of Atrial Fibrillation in the Hospital in 2011-2012 and 2016-2017 (Pharmacoepidemiological Analysis) - O. V. Reshetko; A. V. Sokolov; N. V. Furman; V. V. Agapov (Столичная издательская компания, 2020)
Aim. To study the changes that have occurred in the pharmacotherapy of atrial fibrillation (AF) in the Saratov Region for 5 years by analyzing the antithrombotic therapy of patients who were admitted in a specialized department of the multidisciplinary hospital in Saratov in 2011-2012 and in 2016-2017.Material and methods. A pharmacoepidemiological retrospective study was conducted. The object of the study was the medical records of inpatients (Form 003/y) with the diagnosis "Atrial fibrillation" (ICD-X code I48), that consecutively admitted to the cardiology department of the multidisciplinary hospital in Saratov from January 1, 2011 to December, 31, 2012 (n=211) and from January 1, 2016 to December, 31, 2017 (n=227). Criteria for inclusion in the study: patients over 18 years of age, established diagnosis of non-valvular AF of ischemic genesis. Exclusion criteria from the study: non-ischemic cardiomyopathy, thyrotoxicosis, congenital heart defects, rheumatic heart damage, acute coronary syndrome, endocarditis, myocarditis, pericarditis, pulmonary thromboembolism, the presence of prosthetic heart valve. Pharmacoepidemiological analysis was carried out for the drugs prescribed during hospitalization and given by doctors at discharge of patients from the hospital. The risk of ischemic stroke was assessed using the CHA2DS2-VASc score, and the risk of bleeding - according to the HAS-BLED score.Results. When analyzing the risk of ischemic stroke, it was found that 100% of patients in 2011-2012 years and 98.2% in 2016-2017 years had indications for the prescription of oral anticoagulants (OAСs). In 2011-2012 there were no patients with a low risk of stroke (CHA2DS2-VASc=0). High risk of bleeding (HAS-BLED≥3) occurred in 4.7% of patients in 2011-2012 and in 10.6% in 2016-2017, however, due to the high risk of stroke, the refusal to prescribe OAC in these patients was inappropriate in accordance with the recommendations for the treatment of AF. In the group of patients with CHA2DS2-VASc=0 in 2016-2017 antiplatelet therapy was prescribed in 100% at the hospital stage and at discharge, which contradicts the guidelines, according to which antithrombotic therapy is not recommended to patients with CHA2DS2-VASc=0. In patients with CHA2DS2-VASc=1, a low percentage of anticoagulants prescription was noted. In 2016-2017 OACs were prescribed only in 12.5% of patients at all stages of observation. In 2011-2012 OAC alone was prescribed only to 1 person (20%) at the hospital stage, which does not comply with modern guidelines for the treatment of patients with AF, according to which patients with a risk score CHA2DS2-VASc=1 are recommended to receive OACs in the absence of contraindications. OACs prescription in group CHA2DS2-VASc≥2 occurred only in 15% of patients in 2011-2012 and in a third of patients in 2016-2017 (p<0.05). The frequency of isolated use of OACs significantly increased in 2016-2017 compared to 2011-2012 mainly due to the increase in the spectrum of direct OACs (DOACs) (p<0.05).Conclusion. For 5 years there have been significant changes in the antithrombotic therapy of AF in the Saratov Region. The frequency of prescribing OACs according to indications has increased mainly due to the introduction of the DOACs into clinical practice. However, prevention of stroke remains insufficient.